POLITICAL BRANDING TSAMARA AMANY ALATAS SELAMA MASA KAMPANYE PEMILU LEGISLATIF 2019 DI MEDIA SOSIAL - Rintis Mulyani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Prof Dr Hazairin, SH, 2021)
Social media is a means of disseminating information in marketing candidates or political parties. Politicians do branding through text and images in order to shape people's perceptions of themselves. Political branding on social media can be observed from the choice of words used and the issues discussed. This study aims to analyze Tsamara Amany Alatas' content on her personal social media accounts during the 2019 general election campaign. The researcher adjusted the content uploaded on Instagram and Twitter with the political branding and brand personality that Tsamara formed on his social media accounts. As a result, Tsamara performed all the criteria for successful branding according to the criteria adapted by Needham. Tsamara offers programs that she will strive for clearly, has distinguishing characteristics as a young lady who is brave and ready to be fired by constituents if she is performing poorly, ready to fight for aspirations and ready to be watched, become a symbol of PSI values, and convince constituents that she can trusted in fighting for aspirations. Tsamara has also formed a brand personality as a young politician who is honest and ready to be transparent to constituents, has high empathy especially for women, is brave, smart and has a technical understanding of constituent problems, and is tough. There are differences in the types of content that Tsamara produces on her Instagram and Twitter social media accounts. Tsamara's Instagram content focuses on forming her political brand, while Twitter content focuses on responding to social and political issues at the time and interacting with supporters. This difference is in accordance with the differences in the superior features of the two social media. Twitter is more interactive, allowing Tsamara to interact and discuss, while Instagram makes it easier for Tsamara to focus on delivering political messages to find voice support for her